Analysis of power transfer limit considering thermal balance of overhead conductor. Issue 14 (1st November 2015) - Dong, Xiaoming; Kang, Chongqing; Sun, Hua; Zhang, Ning
Abstract : Series resistances of overhead transmission lines (OTLs) are largely dependent on the corresponding conductor temperature. The electric current heats the conductor, and the environmental conditions affect the thermal exchange. Therefore, multiple factors related to the thermal balance codetermine the conductor temperature and resistance. However, the traditional power flow analysis neglects the thermal balance effects by treating those related factors as invariables, which may introduce some errors because of the change of the factors. Therefore, in this study, new power flow formulations, which allow for the relationship between the transmission power flow and the thermal balance, are derived. This study demonstrates the errors by applying the new formulations to calculate the power transfer limit (PTL). Moreover, the PTL of the OTL is defined either by encountering the thermal rating (TR) or the steady‐state stability limit. A case study based on an equivalent 2‐bus test system was used to illustrate the efficacy of the thermal balance that affects the PTLs of both types. In this analysis, this study also reveals the relationship between the TR and steady‐state stability limit with various physical and environmental conditions.